Improvement plans and their influence on learning indicators in engineering education - Fuentes Maza, Frans (2025)
The purpose of this research was to analyse the influence of the improvement plans on the learning indicators measured in the subjects Electropneumatic Automation and Transformers and Transmission Lines taught in the professional career of Mechanical and Electrical Engineering at the National University of Jaén, Cajamarca, Peru. The improvement plans are aimed at strengthening the quality of the teaching-learning process and were implemented starting in 2020. The measurement and evaluation of learning was carried out according to the following stages: definition of the educational objectives of the programme, construction of the matrix of the contribution of the subjects in the learning indicators, selection of the subjects and elaboration and implementation of the improvement plans. The learning indicators obtained from the implementation of the improvement plans were processed following the established guidelines for an analysis of variance and Tukey's multiple comparisons test, obtaining evidence that indicates the existence of highly significant differences when comparing semesters and learning indicators with respect to the percentage of the level of achievement reached, which reflects the influence of the improvement plans that acquire a continuous character when applied semester after semester